The Impact of Using Slang on Indonesian Language Skills Among Students at Medan State University - Sadewo, Bayu; Lubis, Cahaya Suri; Ghifari, Izhar; Marpaung, Marisa (EDUCTUM: Journal Research, 2024)
This study aims to explore the impact of slang language use on Indonesian language skills among students at Medan State University. Through a quantitative approach with a descriptive survey method, this study collected data from 54 student respondents aged between 18 and 22 years. The survey results showed that most students are more comfortable using slang in everyday conversations, although they are aware of the importance of maintaining good and correct Indonesian language skills. Around 51.9% of respondents stated that steps need to be taken to reduce the use of slang in academic contexts. In addition, more than 50% of respondents also acknowledged the potential negative impact of slang on Indonesian language identity in the future. Based on these findings, this study emphasizes the importance of a balance between the use of slang and formal language, as well as the need for awareness to improve Indonesian language skills among students, in order to support the success of effective communication in various situations, both informal and formal.